Culture and corporate social responsibility in China - Poh, Yang Qian (2014)
Corporate Social Responsibility (CSR) has garnered widespread attention globally over the past few decades as more corporations become more conscious of the extensive benefits it brings when CSR is being incorporated into business models. CSR has gradually evolved from a concept which encompasses only societal contributions to a business strategy.